Subverzija ali asimilacija? - Almasy, Karin (Slavistična revija, 2010)
The article is discussing the anthology "Slowenische Novellen", a collection of six novels written by famous Slovene authors in a german translation. Of special interest is the political, cultural and linguistic background: the anthology was published in 1940 by the publishing house Adolf Luser Verlag in Vienna, which had strong connections to National Socialism and its ideology. The main questions to answer are: Why were these novels published and how were they translated, by whom and under which circumstances? Was it an attempt to absorb these Slovene authors and present them in accordance with national socialist ideology? Or was it contrarily an attempt by the translator to palm these "dubious" authors off an a National ssocialist publisher? The emphasis is on how and for which purpose the translation was made and the roleof translator.
Keywords: 1940; Adolf Luser Verlag; antologije; Austria; Avstrija; ideologija; kratka proza; novela; prevodi v nemščino; Slovene literature; slovenska književnost; Slowenische Novellen